Alinhamento entre prioridades estratégicas competitivas e de produção: um estudo exploratório no polo de calçados infantis de Birigui-SP. - Carvalho, Glauco José de (Universidade Federal de São Carlos, 2017)
Thinking about organizational strategies today is not an easy task, either because of the complexity of the scenarios presented or because of the multiplicity of approaches present in the vast literature on the subject. In the dynamics of global markets, the strategic management of productive operations gains evidence as an essential practice to obtain competitive advantage in organizations. In this context, if the organizational strategy is designed without considering the internal and external environment of the organization, nor the importance of strategic alignment, the company runs the risk of maintaining costly and inefficient activities and processes that can generate unnecessary costs and waste valuable organizational resources . This paper deals with the main concepts of competitive strategy and production, and its main objective is to analyze the competitive and production strategies of companies in the industrial footwear sector of the Birigui-SP region and show evidence of strategic alignment from a proposed conceptual framework. The study adopted a qualitative quantitative research approach through triangulation, associating the survey methods and the case study. The results were significant, through which it was possible to identify the competitive and production strategies of some footwear companies, as well as to consolidate evidence of strategic alignment involving a footwear company and three of its main suppliers.
Alignment between competitive and production strategic priorities: an exploratory study in the infantile footwear industry of Birigui-SP.
Keywords: Estratégia competitiva; Estratégia de produção; Alinhamento estratégico; Indústria de calçados; Competitive strategy; Production strategy; Strategic alignment; Footwear industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO